The Portrayal of Yoo Ah-rin as Mother-like Figure in Webtoon Cewekku Galak - Meugreed Nadia Siliba; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2025)
What happens when a character exemplifies the essence of nurturing, protection, and unconditional love? In the webtoon Cewekku Galak, Yoo Ah-rin emerges as a mother-like figure whose defining traits such as nurturing, protecting, and unconditionally loving profoundly shape the lives of people around her. This study will be using Carl Jung’s mother archetype theory, John Bowlby’s attachment theory, and Melanie Klein’s object relations theory to explore how these qualities foster emotional security, stability, safety, trust, and a sense of acceptance in other characters. At the same time, it reveals the unintended consequences of her care, such as emotional dependency and obsession. By analyzing the dual impact of her role, this research highlights the complexity of maternal figures in fiction and the enduring significance of unconditional love in storytelling.